Pengaruh Latihan Kekuatan Otot Lengan dan Drilling Terhadap Peningkatan Ketepatan Pukulan Overhead Lob - Bahari, Dewa Adi; Widiyatmoko, Fajar Ari; Fahmi, Donny Anhar (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2023)
This research was motivated by problems including the lack of arm muscle strength, arm muscle explosive power and overhead lob punches possessed by athletes aged 9-17 years in PB. Walet Pati city. The aim of the research was to determine how much influence push-up and lob drilling exercises had on increasing the accuracy of overhead lob punches in athtletes PB. Walet Pati city. Type of quantitative research with experimental methods. The research design in one group pretest-posttest design to find out the comparison tesults of the pretest and posttest after the researcher has carried out treatment for 12 meetings. Population of 20 athletes, purposive sampling. Results highest pretest with interval (36 X ≤ 53) has a frequency of 15 athletes, namely 75%. Highest posttest results with intervals (54 X ≤70) in the category (good eneugh) the frequency of 6 athletes is 30%. The lowest posttest results were in the (fair) score interval category (36 X ≤ 53) with a frequency of 14 athletes, namely 70%. Pretest score ≤posttest results. This means that there is an increase in push-up and drilling lob training on the accuracy of the overhead lob strokes of PB. Walet Pati city athletes. The results of the paired samples t-test using the SPSS application swow that the accurary of the overhead lob hit is at a significant level, namely Sig.(2-tailed) with a value of .000 meaning ≤ 0.05 so Ho is rejected and Ha is accepted. If Ha is accepted, it means that there is a significant influence from push-up and drilling lob training on increasing the accuracy of overhead lob strokes in athletes aged 8-17 years PB. Walet Pati city.